2005
DOI: 10.1117/1.1911847
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mid-infrared and Raman spectroscopy in the quantitative analysis of serum

Abstract: Mid-infrared or Raman spectroscopy together with multivariate data analysis provides a novel approach to clinical laboratory analysis, offering benefits due to its reagent-free nature, the speed of the analysis and the possibility of obtaining a variety of information from one single measurement. We compared mid-infrared and Raman spectra of the sera obtained from 247 blood donors. Partial least squares analysis of the vibrational spectra allowed for the quantification of total protein, cholesterol, high and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 23 publications
1
86
0
Order By: Relevance
“…For extensive spectral interference, alternative embedding media [80], more advanced spectral subtraction methods [74], or even greater numbers of specimens can be sought to detect differences between different experimental groups. Because of the small portion of scattered light, Raman acquisition times can be one to two orders of magnitude higher than those typically used in infrared spectroscopy [40,62]. This significant limitation in acquiring large Raman images of bone might be particularly important if heterogeneity of bone tissue composition is eventually proven to be a major contributor to fracture resistance (ie, to bone quality).…”
Section: Introductionmentioning
confidence: 99%
“…For extensive spectral interference, alternative embedding media [80], more advanced spectral subtraction methods [74], or even greater numbers of specimens can be sought to detect differences between different experimental groups. Because of the small portion of scattered light, Raman acquisition times can be one to two orders of magnitude higher than those typically used in infrared spectroscopy [40,62]. This significant limitation in acquiring large Raman images of bone might be particularly important if heterogeneity of bone tissue composition is eventually proven to be a major contributor to fracture resistance (ie, to bone quality).…”
Section: Introductionmentioning
confidence: 99%
“…[62,[67][68][69] and limitations due to the presence of water are often quoted in recently published materials [70]. Therefore, in the present study, different approaches will be described and proposed as alternatives in order to demonstrate and highlight the feasibility to record high quality data without the requirement for water free samples.…”
Section: Biophotonicsmentioning
confidence: 99%
“…In both Infrared and Raman spectroscopic studies, to date the analysis has predominantly been performed on air dried drops of serum deposited on spectroscopically neutral substrates such as CaF 2 [62,63] . The main reasons is the relatively low concentration of analytes in the serum, leading to poor signal to noise ratios from liquid body fluids (Raman spectroscopy) or the strong contribution of water in the spectra collected (Infrared spectroscopy).…”
Section: Biophotonicsmentioning
confidence: 99%
“…Studies have shown that a wide variety of optical methods may be suitable for a reagent-free observation of glucose [64], such as polarimetry or refractometry. Spectroscopy of the molecular vibrations of glucose by IR or Raman spectroscopy [65][66][67] has been shown to be a sensitive and specific method in vitro [68,69] and ex vitro [70]. Raman spectroscopy (employing a 785 nm laser) detected minute amounts of glucose in diluted (10-fold) urine, with a 92% accuracy to classify abnormal (8 mg/dL) and normal urine samples according to their glucose concentrations [71].…”
Section: Diabetesmentioning
confidence: 99%